Why More Americans Have No Religious Preference: Politics and Generations - Hout, Michael; Fischer, Claude S. (American Sociological Review, 2002)
The proportion of Americans who reported no religious preference doubled from 7 percent to 14 percent in the 1990s. This dramatic change may have resulted from demographic shifts, increasing religious skepticism, or the mix of politics and religion that characterized the 1990s. One demographic factor is the succession of generations; the percentage of adults who had been raised with no religion increased from 2 percent to 6 percent. Delayed marriage and parenthood also contributed to the increase. Religious skepticism proved to be an unlikely explanation: Most people with no preference hold conventional religious beliefs, despite their alienation from organized religion. In fact, these “unchurched believers” made up most of the increase in the “no religion” preferences. Politics, too, was a significant factor. The increase in “no religion “ responses was confined to political moderates and liberals; the religious preferences of political conservatives did not change. This political part of the increase in “nones” can be viewed as a symbolic statement against the Religious Right.